Legal Framework Regulating Switching and Disciplining of Members of Political Parties:: Tanzanian and South-African view-point - John Sebastian Ombella (Lembaga Penelitian dan Pengabdian Kepada Masyarakat, 2023)
Globally, political parties seem to be common vehicle through which general public participates in governmental decision-making. This is influenced by the increased democratization evidenced by many countries’ adoption of multipartyism. Consequently, South Africa’s (SA) and Tanzania’s legal frameworks are not exception. Despite such influence Tanzania in particular, improperly regulate switching and disciplining of members of political parties. Through a human right approach this paper carries out a comparative review of SA and Tanzanian legal frameworks on regulation of switching and disciplining of members of political parties. The qualitative analysis of documents reviewed shows SA has adopted constitutional principles the basis of which regulation of political parties contribute to popular participation and elimination of improper switching and disciplining of members of political parties. Tanzania’s legal framework is informed by SA on; cessation of political party membership while retaining the membership in decisions making organs and disciplining of members of political parties.